Penerapan Algoritma Naive Bayes untuk Perbandingan Sentimen Ulasan Lazada dan Tokopedia - Prasetya, Rafli; Hananto, April Lia; Novalia, Elfina; Tukino, Tukino (STMIK Banjarbaru, 2025)
The e-commerce sector is one of many aspects of life influenced by advancements in information and communication technology. Tokopedia and Lazada, as two popular platforms in Indonesia, are increasingly accessed through mobile applications. User reviews serve as valuable input for improving service quality and user satisfaction. This study aims to evaluate user sentiment toward the Lazada and Tokopedia applications on the Google Play Store using the Naïve Bayes algorithm. A total of 2,000 review data were collected using web scraping methods and underwent preprocessing, resulting in 1,864 data points ready for analysis. The Hold-Out technique was applied for data splitting to assess model performance. The results show an accuracy of 89% for both applications. The majority of user sentiment is positive, with Lazada achieving a precision of 94%, recall of 93%, and F1-score of 94%, while Tokopedia achieved a precision of 97%, recall of 86%, and F1-score of 91%. These findings demonstrate the effectiveness of combining the Naïve Bayes algorithm and the Hold-Out technique in sentiment classification.Keywords: E-commerce; Sentiment Analysis; Google Play Store; Naïve Bayes AbstrakSektor e-commerce adalah salah satu dari banyak aspek kehidupan yang dipengaruhi oleh kemajuan teknologi informasi dan komunikasi. Tokopedia dan Lazada sebagai dua platform populer di Indonesia, semakin sering digunakan melalui aplikasi mobile. Ulasan pengguna menjadi masukan penting dalam meningkatkan kualitas layanan dan kepuasan pengguna. Penelitian ini bertujuan untuk mengevaluasi sentimen terhadap pengguna aplikasi Lazada dan Tokopedia di platform Google Play Store melalui algoritma Naïve Bayes. Sebanyak 2000 data ulasan dikumpulkan menggunakan metode web scraping, kemudian dilakukan preprocessing sehingga diperoleh 1864 data siap analisis. Teknik Hold-Out digunakan dalam pembagian data untuk mengukur performa model. Hasil menunjukkan akurasi sebesar 89% untuk masing-masing aplikasi. Sentimen pengguna mayoritas bersifat positif, dengan Lazada memperoleh presisi 94%, recall 93%, dan skor F1 94%, sedangkan Tokopedia memperoleh presisi 97%, recall 86%, dan skor F1 91%. Temuan ini menunjukkan efektivitas kombinasi algoritma Naïve Bayes dan Hold-Out dalam klasifikasi sentimen.